2020
DOI: 10.1038/s41439-020-0095-1
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of a family with XLH with a novel PHEX mutation

Abstract: X-linked hypophosphatemia (XLH) is the most common form of heritable hypophosphatemic rickets. We encountered a 4-year-old boy with a novel variant in the phosphate-regulating neutral endopeptidase homolog X-linked (PHEX) gene who presented with a short stature, genu valgum, and scaphocephaly. The same mutation was identified in his mother and sister; however, the patient presented with a more severe case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…( 20 , 23 , 24 ) Although this introduces the possibility of error due to sex differences, studies with PHEX ‐mutation confirmed XLH have not identified such an effect. ( 24 , 25 ) This study also carries the same limitations of any retrospective analysis, such as ascertainment and recall bias, which may be implicated in the identification of XLH patients in the database used for this study. ( 26 ) As such, we recommend using the results of this study only to supplement standard diagnostic procedures until they are validated in a prospective, multicenter study.…”
Section: Discussionmentioning
confidence: 99%
“…( 20 , 23 , 24 ) Although this introduces the possibility of error due to sex differences, studies with PHEX ‐mutation confirmed XLH have not identified such an effect. ( 24 , 25 ) This study also carries the same limitations of any retrospective analysis, such as ascertainment and recall bias, which may be implicated in the identification of XLH patients in the database used for this study. ( 26 ) As such, we recommend using the results of this study only to supplement standard diagnostic procedures until they are validated in a prospective, multicenter study.…”
Section: Discussionmentioning
confidence: 99%
“…2). (3)(4)(5)(12)(13)(14)(15)18,(20)(21)(22)(23)(24)31,32,(36)(37)(38)(39) There are, however, reports of children with XLH born with features of craniosynostosis. (21,23)…”
Section: Presentation and Diagnosis Of Craniosynostosis In Xlhmentioning
confidence: 99%
“…The exact mechanism of development is still unclear; it is assumed that the mutated gene contains the building instructions for a membrane protein that regulates the recovery of phosphate in the kidney via fibroblast growth factor (FGF)23 [ 9 ]. The mutation is based on the PHEX gene, where disturbed PHEX protein will be expressed [ 7 ].…”
Section: To the Editormentioning
confidence: 99%
“…As a result of the mutation on the PHEX gene, FGF23 overactivity impairs this recovery [ 1 , 4 , 8 , 9 , 21 ]. FGF23 derives from the FGF19 subfamily [ 4 , 7 ]. In the kidney, a klotho-FGFR1-FGF23 trimeric complex will be built with activation of the mitogen-activated protein kinase (MAPK) pathways [ 9 ].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation